Control of co-axial UAV - Ong, Yi Yang. (2010)
Over the period of 1 year, an unmanned coaxial helicopter would be designed and tested. The aim of the project is to achieve an unmanned hover. In process, a suitable coaxial helicopter which could carry the electronics payload, which are being used to control the helicopter for an unmanned flight is to be sourced. Tests are done to check that the electronics and the helicopter can be integrated together to achieve the aim of the project. In this report, research, testing and results of the development of an unmanned coaxial helicopter will be consolidated and explained. Issues encountered during each phase of the development progress are noted down so as to prevent similar mistakes from happening in the future in the development of the project.